WHO IS MORE EAGER TO LEAVE? DIFFERENCES IN EMIGRATION INTENTIONS AMONG LATVIAN AND RUSSIAN SPEAKING SCHOOL GRADUATES IN LATVIA - Varpina, Zane; Fredheim, Kata; Krumina, Marija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Data on migration flows suggest that young people are highly mobile. Yet, there are gaps in the evidence concerning the factors driving young people’s international migration in Latvia. Latvia is a potentially interesting case because of the high rate of migration from the country, but also because it is a complex ethnic and linguistic environment. Latvian and Russian speaking populations are shown to have diverse migration drivers, and this study addresses the differences in attitudes to studying and living abroad for adolescents at the time of school graduation. Literature suggests that Russian-speaking population have higher propensity to emigrate. We aim to contribute to the literature by exploring differences in migration intentions between Latvian and Russian speaking high school graduates.This study is based on individual-level survey data of secondary school graduates in Latvia in 2020, amidst COVID-19 pandemic. We analyse the strength of migration intentions from definitely not leaving Latvia to surely planning to emigrate. We conclude that Russian-speakers exhibit stronger intentions to emigrate compared Latvian-speaking youngsters, driven by wider networks and expected higher returns to their human capital abroad.